Can degradation products released from dental implants affect peri‐implant tissues?. (2nd August 2017) - Noronha Oliveira, M.; Schunemann, W. V. H.; Mathew, M. T.; Henriques, B.; Magini, R. S.; Teughels, W.; Souza, J. C. M.
Abstract : This study aimed to assess the literature available on the effects, on peri‐implant tissues, of degradation products released from dental implants as a consequence of therapeutic treatment for peri‐implantitis and/or of wear‐corrosion of titanium. A literature review of the PubMed medline database was performed up to December 31, 2016. The following search terms were used: "titanium wear and dental implant"; "titanium corrosion and dental implant"; "bio‐tribocorrosion"; "peri‐implantitis"; "treatment of peri‐implantitis"; "titanium particles release and dental implant"; and "titanium ion release and dental implant". The keywords were applied to the database in different combinations without limits of time period or type of work. In addition, the reference lists of relevant articles were searched for further studies. Seventy‐nine relevant scientific articles on the topic were retrieved. The results showed that pro‐inflammatory cytokines, infiltration of inflammatory response cells and activation of the osteoclasts activity are stimulated in peri‐implant tissues in the presence of metal particles and ions. Moreover, degenerative changes were reported in macrophages and neutrophils that phagocytosed titanium microparticles, and mutations occurred in human cells cultured in medium containing titanium‐based nanoparticles. Debris released from the degradation of dental implants has cytotoxic and genotoxic potential for peri‐implant tissues. Thus, the amount and physicochemical properties of the degradation products determine the magnitude of the detrimental effect on peri‐implant tissues.